Caracterização bioquímica, biológica e estrutural de uma quitinase recombinante de chromobacterium violaceum - Lobo, Marina Duarte Pinto (2012)
Chromobacterium violaceum is a Gram-negative, saprophytic, non-pathogenic and free living bacterium. The complete sequencing of its genome has revealed many genes encoding products of biotechnological interest. Among these products are several chitinases. Chitinases, enzymes capable of degrading chitin, an insoluble polymer of β(1,4)-linked N-acetyl-β-D-glucosamine (GlcNAc), are of great biotechnological interest, because they can be used to convert chitin in useful derivatives as well as being exploited for the control of fungi and insects that cause damages in crops. This study aimed to carry out the biochemical, biological and structural characterization of a recombinant chitinase, belonging to family GH18, from C. violaceum ATCC 12472. The ORF CV2935 was amplified by polymerase chain reaction (PCR) and cloned into the vectors pET303/CT-His and pPICZαA, for expression in Escherichia coli and Pichia pastoris, respectively. In both systems, the enzyme was secreted into the culture medium, in its soluble and functional form, and purified to homogeneity by affinity chromatography on a chitin matrix followed by size-exclusion chromatography on Superdex75 matrix. The yields of pure chitinase expressed in E. coli and P. pastoris were 2.6 and 44 mg per liter of culture, respectively. The recombinant chitinase produced in both microrganisms showed optimal activity at pH 3.0 and it was active after treated at temperatures up to 60 °C. The enzyme produced in P. pastoris (45 kDa) was N-glycosylated as revealed by Schiffʼs reagent and digestion with N-glycosidase F. Moreover, the glycosylated chitinase was found to be slightly more thermostable than the enzyme produced in E. coli (43 kDa). The rCV2935 showed hydrolytic activity against colloidal chitin, crab shell, and synthetic substrates containing p-nitrophenol. It was also able to hydrolyse glycol-chitin in SDS-PAGE and showed low chitosanase activity. The fluorescence spectra revealed that the proteins were produced in their folded conformation. The crystal structure of the recombinant chitinase produced in P. pastoris was determined by X-ray crystallography at a resolution of 2.1Ǻ. Its catalytic domain adopts an (β/α)8 triose-phosohate isomerase (TIM) barrel fold, and the residues essential for catalysis are conserved. The recombinant chitinase reduced the growth of the phytopathogenic fungus Rhizoctonia solani, and bioassays with cowpea weevil Callosobruchus maculatus showed that the rCV2935 possibly interfered with the insect feeding, which resulted in decreased weight of adults. The biochemical, biological and structural studies of rCV2935 may be useful for biotechnological application of this enzyme.